EMPOWERING HOUSEWIVES TO INCREASE INCOME THROUGH MINI TUMPENG MAKING TRAINING IN THE BKOW BUILDING, ACEH PROVINCE - Harbiyah Gani; Aida Fitri (Universitas Muhammadiyah Aceh, 2023)
This community service is for increase knowledge and insight regarding making tumpeng rice so that housewives not only take care of the family at home, but have skills and skills that can be used to increase family income. benefit. The output obtained from this community service activity includes (1) the participants can add knowledge and insight about making tumpeng rice which can be used to increase family income(2) From the results of the training, participants are skilled and have the expertise to sell mini tumpeng rice to the community which in the end will increase family income and understand the content of the material and at the end of the session there is question and answer time, several questions are obtained from participants and the community including: (a) How do you market tumpeng rice in the internal and external environment? (b) How do you develop tumpeng rice so that you can have collaborative relationships with culinary tourism parties in Aceh? Keywords: Making Tumpeng Rice